Religious Practice, Craft Specialization and Status: Towards the Understanding of the Social Role of the Hallucinogen Consumption in the Atacama Salt Flat, Northern Chile (500-1500 Ad) [Práctica Religiosa, Especialización Artesanal y Estatus: Hacia la Comprensión del Rol Social del Consumo de Alucinógenos en el Salar de Atacama, Norte de Chile (500-1500 Dc)] - Echeverria-Morgado, J (Universidad Catolica del Norte, 2021)
This work presents the results of a multidisciplinary research focused on the contextual study of the grave goods of six pre-Hispanic cemeteries of the San Pedro de Atacama oasis, Antofagasta Region, Chile. The main objective was to deepen the social and ritual aspects of the prehispanic religious system in Atacama (500-1500 AD), based on the archaeological evidence of the hallucinogenic paraphernalia to elucidate the identity of the individuals carrying it and verify the hypothesis about their status as members of the Atacamenian elite. Databases with the information transcribed from the Le Paige Notes for these cemeteries served as a basic instrument; from them, the statistical analysis was structured according to artifact categories that allowed us to establish correlations between the different components of the mortuary offerings, comparing those that included elements of the psychotropic equipment with those that lacked them. Thus, differences emerged in the management of certain goods that made up the “circle of materializing objects” of the Atacamenian elite. The foregoing raises the existence of different artisan specializations between ayllus and status diferences within this society, as well as the control of interregional exchange circuits by said elite. © 2021. All Rights Reserved.